Reflections on the role of mediators and arbitrators: Can a good mediator also be a good arbitrator? - Evans, Philip; Moens, Gabriel (Macquarie University, Division of Law, 2009)
On 1 January 2008, a National Mediator Accreditation System (NMAS) came into operation in Australia. Mediators can now apply to be accredited by a Recognised Mediation Accreditation Body (RMAB) which will assess applicants under uniform Practice and Approval Standards in relation to mediator competence, including education, training, experience and insurance, as well as a commitment to continuing training.